Web-Based Management Of Perfume Distribution At Aishalina Fragrance Business Using The Economic Order Quantity (EOQ) Method - Agung Pranata; Jusmardi; Yeka Hendriyani; Ahmaddul Hadi (PT. Padang Tekno Corp, 2026)
The perfume industry in Indonesia has shown significant growth in line with the increasing consumer demand for beauty and fragrance products. One of the emerging businesses in this sector is Aishalina, a small and medium enterprise (SME) that focuses on the production and sale of affordable perfumes. However, Aishalina faces several challenges in its distribution process, including suboptimal inventory management, delivery delays, and inefficiencies in supply chain management. To address these issues, this study proposes the implementation of a web-based information system integrated with the Economic Order Quantity (EOQ) method. This system aims to automate the distribution process, monitor stock levels in real-time, and determine the optimal order quantity to minimize inventory-related costs. With a more efficient distribution system, Aishalina is expected to improve service speed, maintain product availability, and enhance customer satisfaction. The results of this study indicate that the implementation of a web-based information system using the EOQ method significantly contributes to improving operational efficiency and increasing the competitiveness of Aishalina in an increasingly competitive market.